Efficacy of a smoking prevention programme in Catalan secondary schools: a cluster‐randomized controlled trial in Spain. (30th January 2015) - Valdivieso López, Empar; Rey‐Reñones, Cristina; Rodriguez‐Blanco, Teresa; Ferre Grau, Carmen; Arija, Victoria; Barrera Uriarte, Maria Luisa; Granado‐Font, Esther; Flores‐Mateo, Gemma; the TAB_ES Study Group
Abstract Aims To evaluate the efficacy of a school‐based educational programme in reducing the incidence and prevalence of smoking in secondary school students (compulsory secondary education: CSE) in Catalonia (Spain). Design Cluster‐randomized controlled trial. Setting Schools in the Tarragona Health Care Region of Spain. Participants All students enrolled in the first year of CSE during the 2007–08 school year in the 29 participating schools (n = 2245); 1583 students completed the follow‐up over the 4‐year study period (804 and 779 in the control and intervention groups, respectively). Measures Self‐reported questionnaires were administered during the first quarter of the 2007, 2008, 2009 and 2010 school years. A smoker was defined as 'smoking cigarettes daily or occasionally within the past 30 days'. Multi‐level logistic regression analysis was conducted to analyse the prevalence and incidence of smoking between the intervention and control groups. Intervention A school‐based educational programme comprising seven modules, each with a different approach to smoking habits. Each module included activities, work‐shops and/or class sessions. Findings The initial prevalence of smokers in the control and intervention groups who completed the follow‐up was 3.9% and 4.2%, respectively. At the end of the study, the prevalence of smokers was 24.4% in the control group and 19.9% in the intervention group. The accumulated incidence of new smokers was 230.57/1000 in the control group and 183.65/1000 in the intervention group. The adjusted odds ratio (OR) comparing the intervention group with the control group was 0.75 [95% confidence interval (CI) = 0.49, 1.15] for smoking prevalence, and 0.74 (95% CI = 0.48, 1.14) for smoking incidence. Conclusions A school‐based educational intervention for secondary school students in Catalonia, Spain was not found to lead to a statistically significant reduction of smoking prevalence and incidence.